Bibliometric Mapping of Climate-Smart Agriculture Research - Loso Judijanto; Dewa Oka Suparwata (Westscience Press, 2026)
Climate-Smart Agriculture (CSA) has emerged as a strategic framework for addressing the intertwined challenges of climate change, food security, and sustainable agricultural development. This study aims to map the global research landscape of Climate-Smart Agriculture using a bibliometric approach. Data were retrieved from the Scopus database and analyzed using VOSviewer to examine publication trends, co-authorship networks, institutional collaboration, country partnerships, keyword co-occurrence, overlay visualization, and density mapping. The results indicate that CSA research is strongly anchored in the broader discourse of climate change, with dominant themes including food security, adaptation, mitigation, sustainability, and smallholder resilience. The keyword clustering reveals three major intellectual streams: socio-economic resilience, environmental sustainability, and technological innovation. Overlay analysis shows a temporal shift from early vulnerability and adaptation-focused studies toward more recent research emphasizing smart agriculture, precision farming, and digital climate solutions. Collaboration networks demonstrate strong North–South and South–South partnerships, with India, the United States, Kenya, and Ethiopia emerging as key contributors. Institutional mapping highlights the central role of international agricultural research centers and universities in shaping the field. CSA research reflects a mature and interdisciplinary domain that increasingly integrates technological innovation with sustainability objectives. Future research should prioritize inclusive digital solutions, policy implementation analysis, and stronger collaboration among climate-vulnerable regions to enhance the transformative impact of CSA practices.